A Longitudinal Study on Generalized Anxiety Among University Students During the First Wave of the COVID-19 Pandemic in Switzerland - Amendola, Simone; von Wyl, Agnes; Volken, Thomas; Zysset, Annina; Huber, Marion; Dratva, Julia (Frontiers in Psychology, 2021)
Objective The COVID-19 pandemic and government measures implemented to counter the spread of the infection may be a major stressor affecting the psychological health of university students. This study aimed to explore how anxiety symptoms changed during the pandemic. Methods 676 students (76% females) at Zurich University of Applied Sciences participated in the first (T0) and second (T1) survey waves. Anxiety symptoms were assessed using the Generalized Anxiety Disorder-Scale-7 (GAD-7). Risk and protective factors (e.g., COVID-19-related variables) were examined. Results GAD-7 scores decreased significantly from T0 to T1 (mean change: −0.446, SE = 0.132, 95% CI: −0.706, −0.186, t = −3.371, df = 659, p = 0.001). Participants with moderate-to-severe anxiety score were 20.2 and 15.6% at T0 and T1, respectively. The following positively predicted anxiety: older age, female gender, non-Swiss nationality, loneliness, participants’ concern about their own health, and interaction between time and participants’ concern about their own health. Resilience and social support negatively predicted anxiety. Conclusions Our findings provide information for public health measures and psychological interventions supporting the mental health of university students during the COVID-19 emergency.